Practices and Challenges of Teachers' Professional Development in Cluster Satellites of Haramaya University: Higher Diploma Program in Focus - Abo, Garkebo Basha; Hussein, Anwar Ahmed (Bahir Dar Journal of Education, 2020)
The purpose of this study was to investigate the practices and challenges of teaches’ professional development in cluster satellites of HU. To realize this purpose, a descriptive survey research design was used. The study was carried out on 4 teacher education colleges and 3 universities located in the cluster. 86 (50%) of HDP candidates were included in the sample through stratified random sampling. All HDP leaders, tutors, and coordinators were incorporated through availability sampling technique. Questionnaire, semi-structured interview, focus group discussion, and document analysis were used to collect data. The analysis of quantitative data was carried out by using mean and one-way ANOVA and multiple regressions, while qualitative data was analyzed using thematic approach. The finding of the study revealed that the practice of HDP was low in terms of conducting formal lesson observation and following up HDP graduates to assess the impact of the program on their teaching. Moreover, the study indicated that high workload on HDP candidates, low value given for HDP certificate and using of the same training material for HDP candidates coming from various fields of specialization were found negatively affecting practices of HDP. The implication is that the contribution of HDP in producing pedagogically competent teacher educators will be minimal. Therefore, universities should reduce the workload of HDP trainees and universities, in collaboration with MoE, should contextualize the training material in accordance with the fields of specialization of trainees.